2013
DOI: 10.1371/journal.pone.0055211
|View full text |Cite
|
Sign up to set email alerts
|

ErbB2-Dependent Chemotaxis Requires Microtubule Capture and Stabilization Coordinated by Distinct Signaling Pathways

Abstract: Activation of the ErbB2 receptor tyrosine kinase stimulates breast cancer cell migration. Cell migration is a complex process that requires the synchronized reorganization of numerous subcellular structures including cell-to-matrix adhesions, the actin cytoskeleton and microtubules. How the multiple signaling pathways triggered by ErbB2 coordinate, in time and space, the various processes involved in cell motility, is poorly defined. We investigated the mechanism whereby ErbB2 controls microtubules and chemota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 40 publications
0
24
0
Order By: Relevance
“…Phospholipase C-g, which is stimulated by ErbB2, also converges on Memo and participates in microtubule capture (13). Moreover, we have shown that Memo increases the actin-depolymerizing and actin-severing activity of cofilin (2).…”
Section: Increased Memo Abundance In Breast Cancer Correlates With Agmentioning
confidence: 73%
See 2 more Smart Citations
“…Phospholipase C-g, which is stimulated by ErbB2, also converges on Memo and participates in microtubule capture (13). Moreover, we have shown that Memo increases the actin-depolymerizing and actin-severing activity of cofilin (2).…”
Section: Increased Memo Abundance In Breast Cancer Correlates With Agmentioning
confidence: 73%
“…Memo knockdown decreases directed motility of breast cancer cell lines in Transwell and Dunn chamber assays (1,2,13). We examined the effect of Memo knockdown using wound closure and invasion assays.…”
Section: Memo Is Required For Cell Motility and Invasionmentioning
confidence: 99%
See 1 more Smart Citation
“…These genes include HECTD1 (HECT domain containing E3 ubiquitin protein ligase 1), involved in negative regulation of the Wnt-Axin pathway (Tran et al , 2013), MACF1 (micro-tubule-actin crosslinking factor 1) involved in the regulation of cell migration after ErbB2 stimulation (Benseddik et al , 2013), LOX (lysyl oxidase) involved in creating a fibrotic environment favorable to tumor cell colonization (Cox et al , 2013) and SLC1A3 (solute carrier family 1 [glial high affinity glutamate transporter], member 3) involved in the response to wounding. The genes ADCY2 (adenylate cyclase 2 [brain]) involved in signal transduction from membrane receptors, HNMT (histamine N-methyltransferase) involved in histamine metabolism and USP16 (ubiquitin specific peptidase 16) involved in histone deubiquitination and cell cycle were also found to be more expressed in bone marrow mesenchymal cells.…”
Section: Discussionmentioning
confidence: 99%
“…To analyze microtubules in migrating cells [28][29][30] , SKBr3 cells co-transfected with EGFP-α-tubulin and the indicated siRNA or cDNA were grown on collagen-coated glass coverslips for 48 h and observed 10 min after the addition of 5 nM HRGβ1 (R&D Systems) using the 63X objective (plan Apochromat NA 1.4) of a fluorescence microscope (Zeiss Axiovert 200) driven by MetaMorph 6.3 software. Images were acquired using a CoolSNAP HQ digital camera (Roper) and the percentage of cells showing microtubules extending towards the cell periphery and perpendicular to the cell membrane was calculated in three independent experiments.…”
Section: Methodsmentioning
confidence: 99%